Simultaneous Determination of Rutin, Luteolin, Quercetin, and Betulinic Acid in the Extract of Disporopsis pernyi (Hua) Diels by UPLC - Yanqi Wang; Shuyi Li; Dandan Han; Kehan Meng; Miao Wang; Chunjie Zhao (Journal of Analytical Methods in Chemistry)
Disporopsis pernyi (Hua) Diels, which belongs to genus Disporopsis, has been widely used for the treatment of abnormal sweating, chronic cough, and so forth. An ultra-performance liquid chromatography (UPLC) analysis was developed for the determination of rutin, luteolin, quercetin, and betulinic acid in Disporopsis pernyi (Hua) Diels roots. UPLC analysis was conducted by using a Shim-pack XR-ODS column with gradient elution with the mobile phase of acetonitrile and water containing 0.1% formic acid and with a flow rate of 0.2 mL/min, detected at 210, 254, and 280 nm. The method was precise, with relative standard deviation < 2.0%. The recoveries for the four components in Disporopsis pernyi (Hua) Diels were between 98.5 and 100.9%. The average contents of rutin, luteolin, quercetin, and betulinic acid in roots were 5.63, 2.51, 3.87, and 2.41 μg/g, respectively. The method was accurate and reproducible and it can provide a quantitative basis for quality control of Disporopsis pernyi (Hua) Diels.